The Digital Spirituality and Emotional Da’wah: An Interpretation of Religious Symbols in “Qalbi Fii Madinah” - Pahlevi, Reza (MUHARRIK: Jurnal Dakwah dan Sosial, 2026)
The development of technology and culture has transformed Islamic da'wah from conventional forms into creative and emotional expressions, notably through religious songs. The song “Qalbi Fii Madinah” by Maher Zain and Harris J represents contemporary Islamic music embedded with spiritual symbols and da'wah messages. This study aims to analyze the song as a medium of da'wah by interpreting the religious symbols in its lyrics and visuals, and assessing their compatibility with Islamic da'wah principles. This research employs a descriptive qualitative method using content analysis. The primary analytical framework is built upon Charles Sanders Peirce’s semiotic triadic model representamen, object, and interpretant, while Clifford Geertz’s cultural theory of symbols is utilized strictly as a subordinate contextual reference. Additionally, a normative analysis grounded in Islamic jurisprudential principles is applied to evaluate the permissibility and ethical boundaries of the song's artistic expression. The findings show that the song presents religious symbols representing love for the Prophet Muhammad, longing for Madinah, and an invitation to strengthen spiritual awareness. Normatively, the song aligns with the principles of da'wah bil hikmah and mau'izah hasanah, as its messages are conveyed through ethical, gentle, and spiritually meaningful expressions without contradicting sharia values. Therefore, “Qalbi Fii Madinah” serves as a valid contemporary form of Islamic da'wah that effectively communicates religious values through a structured symbolic and aesthetic musical framework.